2005
DOI: 10.1111/j.1365-2929.2005.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of directed and self-directed learning in evidence-based medicine: a randomised controlled trial

Abstract: This trial and its accompanying qualitative evaluation suggest that self-directed, computer-assisted learning may be an alternative format for teaching EBM. However, further research is needed to confirm this and investigate alternative educational models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(150 citation statements)
references
References 14 publications
(30 reference statements)
3
141
2
4
Order By: Relevance
“…[33][34][35][36][37] However, knowledge is still lacking to assess the effectiveness of e-learning CME. 34 In that regard, this study adds to the developing body of knowledge on learners' experiences with respect to e-learning in the medical sphere by exploring qualitatively the perceptions of different types of e-learners (adopters, partial adopters and non-adopters).…”
Section: Strengths and Limitations Of The Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37] However, knowledge is still lacking to assess the effectiveness of e-learning CME. 34 In that regard, this study adds to the developing body of knowledge on learners' experiences with respect to e-learning in the medical sphere by exploring qualitatively the perceptions of different types of e-learners (adopters, partial adopters and non-adopters).…”
Section: Strengths and Limitations Of The Study Resultsmentioning
confidence: 99%
“…31,32 Indeed, this program addresses the development of individual skills in critical appraisal and EBM and opts for a self-tutorial method of instruction. A recent study 33 found no significant differences between two forms of EBM teaching: one consisting of directed workshops and the other consisting of a selfdirected computer-assisted program. However, selfdirected learning might not suit everyone.…”
Section: Discussionmentioning
confidence: 99%
“…2 Many different strategies have been used for teaching EBDM including lectures, discussion groups, journal clubs, and responding to questions generated during clinical practice experiences. [3][4][5][6][7][8][9] Different outcome measures (knowledge, attitudes and skills) have been used to assess EBDM competence. 10 Some of these measures include: self-report of skills, 11 use of tools to evaluate critical appraisal skills, 4,5 use of validated tools (eg, Fresno and Berlin assessment tool) to assess EBDM skills and knowledge, 5,6 and structured evaluation of answers to actual practice-based clinical questions.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Different outcome measures (knowledge, attitudes and skills) have been used to assess EBDM competence. 10 Some of these measures include: self-report of skills, 11 use of tools to evaluate critical appraisal skills, 4,5 use of validated tools (eg, Fresno and Berlin assessment tool) to assess EBDM skills and knowledge, 5,6 and structured evaluation of answers to actual practice-based clinical questions. [5][6][7][8][9] The University of Wisconsin-Madison School of Pharmacy teaches a semester-long course in drug literature evaluation that focuses on reading and critical appraisal of primary research literature.…”
Section: Introductionmentioning
confidence: 99%
“…1,9,10,12 Various interventions aimed at improving information management knowledge and skills have been implemented, [13][14][15][16][17][18] with most reporting positive findings. In each case, learning was assumed to have occurred.…”
mentioning
confidence: 99%